Aster Sdn. Bhd. / Ezza Ezranee Hamzah ... [et al.] - Hamzah, Ezza Ezranee; Michael, Farah; Jimmy, Herald; Andrew, Juliet Suyin; Eyon, Naomi; Md Yunus, Norliza (Faculty of Office Management & Technology, 2005)
"Water is life." No one understands this better than us. As a supplier of mineral water, we know how important it is for human to have unlimited access of drinking water. It is not just the need to eliminate/quench the thirst but the need to keep your body fresh and energized. As a mineral water supplier, we feel that we are not just selling our product but also a distributor of needs and wants. No one can tell you that they don't need water, for this element are made available no matter what the occasion and situation is. Shah Alam is a city, which caters to all sorts of activity, which is why we feel that Shah Alam is the best place to establish our business.